2009
DOI: 10.1007/s11856-009-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Completely monotone sequences and universally prestarlike functions

Abstract: We introduce universally convex, starlike and prestarlike functions in the slit domain C \ [1, ∞), and show that there exists a very close link to completely monotone sequences and Pick functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Wirths [5] has shown that f ∈ T implies that the function zf (z) is univalent in the half-plane Re z < 1, and recently the theory of universally prestarlike mappings has been developed, showing a close link to T ; see [4]. Many classical functions belong to T or are closely related to it.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wirths [5] has shown that f ∈ T implies that the function zf (z) is univalent in the half-plane Re z < 1, and recently the theory of universally prestarlike mappings has been developed, showing a close link to T ; see [4]. Many classical functions belong to T or are closely related to it.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…Fundamental for the proof of Theorem 1.5 is the following result, which is based on a general theorem in [4].…”
Section: Theorem 13 For F G ∈ T We Havementioning
confidence: 99%
“…Universally starlike functions can also be defined and characterized in an analogous way by means of the class T , see [66] for details.…”
Section: Is Universally Convex If and Only Ifmentioning
confidence: 99%
“…In [3] the notion of prestarlike functions has been extended from the unit disk to other disks and half-planes containing the origin. Let be such a disk or half-plane.…”
Section: Universally Prestarlike Functionsmentioning
confidence: 99%
“…For some general information concerning universally prestarlike functions, in particular about universally convex functions ( f ∈ R u 0 ) and universally starlike functions ( f ∈ R u 1/2 ), see [3].…”
Section: Universally Prestarlike Functionsmentioning
confidence: 99%